If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(9 + x) = 33 (9 * 3 + x * 3) = 33 (27 + 3x) = 33 Solving 27 + 3x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 3x = 33 + -27 Combine like terms: 27 + -27 = 0 0 + 3x = 33 + -27 3x = 33 + -27 Combine like terms: 33 + -27 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 6x-5+5x=61 | | .006s+.02=.2 | | 1-5n=11-3n | | -3x+2(5x+6)=54 | | 5x-34=23+2x | | (n*10)*3=2*(10*3) | | 6x+89=10x-11 | | -3+a-5=-2 | | -11x-104=-2x+31 | | (10-6y+e^3x)dx-2dy=0 | | q=bx+cforx | | -11x-104=-2x+31 | | 7(x-1)=-28 | | 4.4n=30.8 | | 21x-3= | | 11x-15=6+10x | | 46=2x-5x+10 | | 2/3(12)-5=(12)/4 | | 4(x+4)=6x+26 | | 4(6+8+x)= | | -7+7x=-1+7x | | -83+4x=8x+21 | | -2/-1.3 | | j=0+9 | | y=-16t^2+20t+120 | | 3x/4=-2/3 | | 1/4•3 | | -90-3x=-8x+30 | | 168=-v+62 | | 10h+3p= | | 24+12y-36x=O | | 3/5x-5/2=3/4x |